Monitoring the Response of connected moored floating modules - Michailides, Constantine; Loukogeorgaki, Eva; Angelides, Demos C. (My University, 2013)
In the present paper a recently installed Sensor Network for Monitoring the Response (SNMR) of a Floating Structure (FS) is presented. SNMR is deployed on a pontoon-type FS operating as a floating breakwater, located 300m from the coast in the port of Neos Marmaras in Greece. The developed SNMR consists of: (i) sensors for real time measurement of FS's critical response quantities related with the structural integrity and safety of the FS as well as of environmental parameters and (ii) data acquisition and data transfer and storage system. Characteristic examples of time series of the measure quantities obtained during the operation of the SNMR are presented and preliminary assessed. Copyright © 2013 by the International Society of Offshore and Polar Engineers (ISOPE).
Keywords: Sensor Network for Monitoring the Response (SNMR)